Education for Prevention of Alcohol and Tobacco Consumption in Secondary Education in Cubal - Adelino Pena Calei; Augusto José Fazenda (BIRCU, 2019)
The objective of the study was to characterize the current situation of alcohol and tobacco consumption in secondary school, with a view to the health education, in Cubal, Benguela province, Angola. The study was carried out in the first and second trimester of the school year and the survey to the teacher and student, interviews with school principals and participant`s observation during class and in the playground were used as methods. The sample was taken from the Fist Cycle of Secondary Education at